2020
DOI: 10.1021/acs.jpcc.0c08068
|View full text |Cite
|
Sign up to set email alerts
|

Optical Trapping of Photosoftened Solid Polymers

Abstract: We present evidence of optical trapping of solid polymer films by a tightly focused near-infrared (NIR) laser beam (785 nm) when the polymer is softened by green laser (532 nm) irradiation, which is uniformly distributed over the film surface. While the whole film is softened by the green laser, only the part which is subjected to the NIR laser is trapped. The film, which is transparent in the NIR range and strongly absorbs the visible light, is deposited on a glass substrate. The NIR laser is focused at the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Several studies have shown experimentally that photo-induced free volume plays a key role in light-induced motion in azomaterials and that the "photo-softened" material can be manipulated, for instance, through optical tweezers. 12,51,73,74 A detailed model recently published by Sekkat provides a quantitative connection between the absorbed energy dose and the photo-induced decrease in relaxation time, analogous to the effect of temperature on nonirradiated systems. 8 Our group, in an IR spectroscopy investigation, showed that the photo-isomerization of the azobenzene under unpolarized light strongly perturbs the chemical environment around the azo, as expected, whereas it does not affect the chemical environment of molecular moieties located far from the azo such as the polymer chain in the case of a covalent sidechain azopolymer.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Several studies have shown experimentally that photo-induced free volume plays a key role in light-induced motion in azomaterials and that the "photo-softened" material can be manipulated, for instance, through optical tweezers. 12,51,73,74 A detailed model recently published by Sekkat provides a quantitative connection between the absorbed energy dose and the photo-induced decrease in relaxation time, analogous to the effect of temperature on nonirradiated systems. 8 Our group, in an IR spectroscopy investigation, showed that the photo-isomerization of the azobenzene under unpolarized light strongly perturbs the chemical environment around the azo, as expected, whereas it does not affect the chemical environment of molecular moieties located far from the azo such as the polymer chain in the case of a covalent sidechain azopolymer.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Photoisomerization of azobenzene derivatives, induced by resonant laser light irradiation, strongly enhances molecular mobility in azo-polymers by tens to hundreds of °C below T g , a feature that can be rationalized by a photoinduced increase of the nanocogent free volume of the dye, which in turn enhances molecular mobility, and mass motion occurs in gradients of light intensity. Photoisomerization softens the solid polymer, and external potentials due to light intensity gradients move it . Intensity gradients, produced by interference patterns of coherent light beams, can be used as one of such potentials to create motion and spatially arrange the polymer in a periodic manner, i.e., create surface relief gratings (SRGs).…”
Section: Introductionmentioning
confidence: 99%
“…Azo-dye-containing materials have been studied extensively in past decades for applications in holography and optical data storage [28,29], nonlinear optics (NLO), electro-optic modulation (EO), second-harmonic generation (SHG) [30][31][32][33], photomechanical actuation and matter motion, and so on [34][35][36][37][38][39][40]. Azo dyes also have potential applications in dye chemistry and bio-photonics [41,42], driving a natural interest in their optical characterization, namely the determination of the real and imaginary parts of n c as a function of the wavelength of light.…”
Section: Introductionmentioning
confidence: 99%